2020
DOI: 10.1371/journal.pone.0233675
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to bystander CPR in deprived communities: Findings from a qualitative study

Abstract: Study aim Rates of out of hospital cardiac arrest are higher in deprived communities. Bystander Cardiopulmonary Resuscitation (BCPR) can double the chance of survival but occurs less often in these communities in comparison to more affluent communities. People living in deprived communities are, therefore, doubly disadvantaged and there is limited evidence to explain why BCPR rates are lower. The aim of this paper is to examine the barriers to administering BCPR in deprived communities. Method Mixed method qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
2
12
0
1
Order By: Relevance
“…Most participants identified the fear of harassment by police and the medico-legal system.as a barrier and cited lack of laws safeguarding lay rescuers in Pakistan. This finding is similar to studies from China and Scotland, where bystanders feared being caught up in a legal dispute as a barrier [ 17 , 28 ]. Public perception that CPR and other life saving skills should only be performed by medical professionals are further reinforced by policies discouraging bystander engagement.…”
Section: Discussionsupporting
confidence: 87%
“…Most participants identified the fear of harassment by police and the medico-legal system.as a barrier and cited lack of laws safeguarding lay rescuers in Pakistan. This finding is similar to studies from China and Scotland, where bystanders feared being caught up in a legal dispute as a barrier [ 17 , 28 ]. Public perception that CPR and other life saving skills should only be performed by medical professionals are further reinforced by policies discouraging bystander engagement.…”
Section: Discussionsupporting
confidence: 87%
“…There is no speci c law to safeguard and protect the bystanders and rescuers in Pakistan, such as the "Good Samaritan Law." This nding is similar to studies from China and Scotland, where bystanders feared being caught up in a legal dispute as a barrier 36,45 .…”
Section: Discussionsupporting
confidence: 86%
“…The findings of this review informed the analysis of a qualitative research study on bystander CPR with deprived communities in Scotland which identified similar individual and environmental barriers to be targeted through tailored interventions. 50…”
Section: Discussionmentioning
confidence: 99%